Main Differences of Synchronous Translation from Sequential Translation: Advantages and Disadvantages (Texas Journal of Multidisciplinary Studies, 2022)
The article outlines the distinctive features, usage areas, conveniences and disadvantages of synchronous translation from sequential translations and other translations.